Проведення термолюмінесцентного аудиту струменів дистаційних гамма-терапевтичних апаратів у медичних закладах - Озерський, К. Л.; Пустовий, А. С. (ХНУРЕ, 2024)
The quality assurance of gamma therapy is underpinned by metrological support, which includes organizational and technical measures aimed at achieving the accuracy and uniformity of dosimetric measurements. The calibration check of beams from remote gamma therapy devices is carried out using TLD (Thermoluminescent Dosimeter) detectors - plastic capsules filled with TLD powder, which are mailed to radiological centers for irradiation with a certain dose in a water phantom. Based on the measurements of TLD detector signals, conclusions can be made regarding the accuracy of dose delivery on a specific remote gamma therapy device.
Keywords: гамма-терапевтичний апарат; гамма-терапія